Prognostic value of low ankle-brachial index in patients with resistant hypertension - Yu. M. Sirenko; O. L. Rekovets; S. A. Polischuk (Zaporožskij Medicinskij Žurnal)
In the presence of resistant hypertension, patients have a significantly higher risk of stroke, myocardial infarction, kidney disease, heart failure, and death than patients with elevated blood pressure. Increased arterial stiffness is an important factor in determining cardiovascular risk. Peripheral artery damage is a target organ lesion, and its presence puts the patient at high or very high risk. The simplest non-invasive method of detecting peripheral vascular damage in patients is to determine the ankle-brachial index (ABI).